2012
DOI: 10.1111/j.1530-0277.2012.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective Physiological, Psychological, and Behavioral Risk‐Taking Consequences of Alcohol and Energy Drink Co‐Ingestion

Abstract: Co-ingestion may provide a double-edged effect. The increased stimulation from energy drinks (EDs) may negate some intoxication-related sedation side effects by increasing alertness. However, it could also lead to negative physiological side effects associated with overstimulation. Notwithstanding any stimulatory effects of EDs, risk and negative effects of excessive alcohol consumption were present in both session types. However, the odds of engaging in risk-taking were less during AmED sessions relative to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(144 citation statements)
references
References 20 publications
5
127
0
12
Order By: Relevance
“…First, consuming caffeine with alcohol may alter the subjective rewards experienced by the drinker (Peacock et al, 2012), thus increasing alcohol use both in the moment and across time. Second, the observed links may refl ect preexisting differences among people (Howland and Rohsenow, 2013;Peacock et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…First, consuming caffeine with alcohol may alter the subjective rewards experienced by the drinker (Peacock et al, 2012), thus increasing alcohol use both in the moment and across time. Second, the observed links may refl ect preexisting differences among people (Howland and Rohsenow, 2013;Peacock et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Largely absent from the literature are studies reporting on the prevalence of consumption of these drinks and important individual and social correlates. A handful of nonrepresentative, small-sample studies from Canada, the United States, Turkey and Italy have reported on consumption of these drinks among college students and noted that between 15% and 85% of energy drinks users mix them with alcohol.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Our finding that 20% of Canadian high school students had consumed these drinks in the previous year raises a number of important questions about how best to move forward. Given that individuals who use alcohol mixed with energy drinks, relative to alcohol alone, are less able to recognize the symptoms of intoxication, and report greater risk-taking, higher susceptibility to injury and increased alcohol consumption in the short term, along with neurologic complications and higher alcohol dependence, 1,16,[22][23][24][25][26][27][28][29][30][31] opportunities to intervene by health policy-makers, clinicians and programmers responsible for youth are necessary. Health Canada, along with the US Food and Drug Administration (FDA), warn against the mixing of energy drinks with alcohol, and the FDA has moved to eliminate such "premixed" beverages from the market.…”
Section: Policy Implications and Future Researchmentioning
confidence: 99%
“…Design and Methods: A meta-analysis of studies applying a withinsubject comparisons among AMED consumers comparing alcohol consumption on occasions when they consume AMED versus alcohol only occasions. Results: Four studies were identified [1][2][3][4], including 1802 AMED consumers. The meta-analysis showed no significant difference in overall alcohol consumption between AMED and alcohol only occasions (P = 0.783, 95% confidence interval -0.191 to 0.253).…”
Section: Paper 88mentioning
confidence: 99%